The Meaning of Non-Precious Material Jewelry and Its Relation to Anxiety in Urban Socialite Women - Dhyani Widiyanti (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Yogyakarta, 2024)
The research entitled The Meaning of Non-Precious Material Jewelry and Its Relation to Anxiety in Urban Socialite Women is intended to analyze the non-precious material jewelry worn by these women in Jakarta and its relation to the state of anxiety they experience. This research is qualitative research that uses semi-structured interviews with six informants who are selected based on purposive sample criteria. The results of the interviews were analyzed utilizing Zygmunt Bauman's theory as written in Liquid Fear (2006). The conclusions of this study indicate that socialite urban women consider the ownership and use of non-precious material jewelry as not mere accessories but is associated to a deeper meaning. Socialite urban women experience a state of anxiety both internally and externally. The possession and use of non-precious material jewelry is an effort to overcome anxiety which is connected to identity and uncertainty. Socialite urban women make the possession and use of non-precious material jewelry as a way to have fun, an escape from